Sebaran komunitas ikan padang lamun (seagrass beds) pada musim barat di perairan pesisir Kota Bontang, Kalimantan Timur: Fish community distribution on seagrass beds during west season in coastal waters of Bontang City, East Kalimantan - Jailani (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2022)
This research was aimed to describe the dynamic of fish community on seagrass beds and to identify the distribution. The study was located in the coastal waters of Bontang during west season with 4 sampling stations. The total number of captured fish was 378 individuals. Correspondence analysis approach was applied to determine the distribution. The result shows that there is similarity between location A and B, while C and D is also identified closely similar. This result also indicated that uniformity factor of habitat and environment characteristic is most likely the major cause of fish diversity that associated to dynamic and varied seagrass beds.